Highly Sensitive Terahertz Metamaterial Sensor - Saadeldin, A. Samy; Hameed, Mohamed Farhat O.; Elkaramany, Essam M. A.; Obayya, Salah S. A. (IEEE sensors journal, 2019)
A novel design of nearly perfect metamaterial absorber is proposed and analyzed for terahertz sensing applications. The full vectorial finite element method is used to simulate and analyze the reported design. The suggested structure is based on increasing the confinement of both electric and magnetic fields simultaneously at the resonance frequency. Therefore, an absorptivity of 0.99 is achieved at 2.249 THz with a narrow resonant peak and a Q -factor of 22.05. The resonance frequency is sensitive to the surrounding medium refractive index at fixed analyte thickness. Consequently, the reported metamaterial design can be used as a refractive index (RI) sensor with the high sensitivity of 300 GHz/RIU and the figure of merit (FoM) of 2.94 through an RI range from 1.0 to 1.39 at the analyte thickness of 1.0~ μ \text{m} . Furthermore, the proposed sensor has a sensitivity of 23.7 GHz/ μ \text{m} for the detection of the sensing layer thickness variation at the fixed analyte RI of 1.35. It is worth noting that most of the biomedical samples have a refractive index range from 1.3 to 1.39. Therefore, the reported sensor can be used for biomedical applications with high sensitivity.